Technical Note: Abrasive Waterjet Cutting Application - Higgins, Christopher C.; Newell, James D. (Engineering Journal, 2004)
Abrasive waterjet cutting is a relatively little used technique for fabrication of structural steel components. The technique may permit economical fabrication of earthquake resistant structural steel members such as core elements of buckling-restrained braces. Abrasive waterjet cutting was used to fabricate yielding core elements for a new type of buckling-restrained brace. A 50,000 psi (344.7 MPa) waterjet and garnet abrasive cutting stream was computer numerically controlled to cut dog-bone and perforated yielding core configurations in 3/4 in. (19.05 mm) and 1-1/4 in. (31.75 mm) A36 steel bar stock. Abrasive waterjet cutting is a cold process and does not produce the heat affected zone associated with oxyfuel or plasma cutting. Tension coupon testing of a small number of samples of both traditionally machined and abrasive waterjet cut specimens indicated little change in the ultimate stress and only slightly reduced yield stress and total elongation for abrasive waterjet cut A36 steel coupons.